Kontribusi Tenaga Kerja Dalam Keluarga Terhadap Pendapatan Usahatani Terong (Solanum melongena L.) Di Kelurahan Landasan Ulin Utara Kecamatan Liang Anggang Kota Banjarbaru - Yan Yozef Agus Suratman (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2015)
The purpose of this study were (1).find out view of  eggplant cultivation farms, (2) Using labor in the family, (3). real costs, revenues, and earnings, (4) .kontribusi family workers against eggplant farm income in the Village of Runway North Ulin. Research using survey method with observation technique. Sampling method using census method, growers example 25 farmers. The research result is the production of an average of 1453.28 kg with an average land area of 4.48 borong or converted into 12.11 tonnes per hectare. Outpouring of labor within the family at this eggplant farming an average of 86.11 percent. Explicit costs an average of Rp. 619,134.00 / respondent (Rp. 60,079,794.79 / ha), receiving an average of Rp. 3,963,520.00 / respondent (Rp. 33,029,333.33 / ha), and the average income of Rp. 3,344,386.00 / respondent (Rp. 27,869,883.33 / ha). The amount of the contribution of labor in average family farm income against eggplants amounted to 27.86%.